Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan Toko Buah Risman di Pasar MMTC Medan - Mahya Sabilillah; Putri Sandrina Sitompul; Radhika Narwastu; Nafidza Shadrina (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
This study aims to analyse the effect of service and product quality on customer satisfaction at Risman fruit shop in the MMTC Medan market. The research method used is quantitative research involving 35 respondents. This study uses multiple linear regression as an analytical tool to see the effect of each variable. Service quality indicators are tangibility, reliability, responsiveness, empathy and service assurance. This study’s product quality indicators are product freshness, product presentation and taste quality. Customer satisfaction indicators are the conformity of expectations and reality, the interest in repurchasing, and the willingness to recommend. The results showed that service quality and product quality significantly influence customer satisfaction. These findings imply the importance of improving service and product quality to increase customer satisfaction at Risman fruit shop. This study provides valuable insights for similar business owners and marketing managers to improve relationships with customers and enhance business performance.